2011
DOI: 10.1111/j.1600-0501.2010.02127.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bone grafting material and a collagen membrane in the ridge splitting technique: an experimental study in dogs

Abstract: After ridge splitting, if the gaps between implants were grafted or covered with collagen membranes, a higher percentage of BIC was obtained. Based on our results, we suggest that the use of bone graft materials and/or collagen membranes is better for the prevention of MBL after ridge splitting procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 49 publications
5
48
1
3
Order By: Relevance
“…After ridge splitting, fixation with miniscrews is optional and the decision depends on the mobility of the buccal cortex. Fixation of the buccal cortex and grafting of the gap between cortical bone walls increase stability and decrease bone loss in alveolar ridge splitting 18. In the present case, two cylindrical bone blocks were used to stabilize the alveolar ridges in their expanded positions, for autogenous bone grafting and achieving stable buccal cortical bone.…”
Section: Discussionmentioning
confidence: 95%
“…After ridge splitting, fixation with miniscrews is optional and the decision depends on the mobility of the buccal cortex. Fixation of the buccal cortex and grafting of the gap between cortical bone walls increase stability and decrease bone loss in alveolar ridge splitting 18. In the present case, two cylindrical bone blocks were used to stabilize the alveolar ridges in their expanded positions, for autogenous bone grafting and achieving stable buccal cortical bone.…”
Section: Discussionmentioning
confidence: 95%
“…In a 30-patient clinical study, the use of biomaterials reduced horizontal loss, but not vertical loss, of the buccal wall [11]. Other studies have demonstrated that vertical bone loss was limited using an allograft covered with a resorbable collagen membrane [1012131415161718]. Clearly, biomaterials delay osseointegration during the time of reossification during new bone-implant contact.…”
Section: Introductionmentioning
confidence: 99%
“…Pure cortical allograft particles provide the density and strength of an autograft of cortical bone without the cost or invasiveness of that method. Therefore, the renewed interest of clinicians in allografts, with or without a collagenous membrane, justifies new in-depth studies of this material [131518]. Our study focused on cortical bone chips, which have not been previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…Assim, a migração dos osteoblastos é facilitada, acelerando o processo de regeneração (HAN et al, 2011).…”
Section: Osso Bovino Inorgânico Com Colágenounclassified
“…Essa maior quantidade de proteínas propicia melhores propriedades mecânicas aos enxertos, facilitando sua manipulação no transoperatório como desgastes para a adaptação e fixação com parafusos, sem ocorrer fraturas do bloco. Segundo Han et al (2011) o colágeno também serve como ponte de ligação entre as partículas do enxerto e a parede do defeito e estabiliza as partículas ósseas, facilitando a migração celular.…”
Section: Gruposunclassified